Microfirms and innovation in the service sector - David B. Audretsch; Alexander S. Kritikos; Alexander Schiersch (Small Business Economics, 2020)
In the context of microfirms, this paper analyzes whether the link between the three aspects involving innovative activities—R&D, innovative output, and productivity—hold for knowledge-intensive services. With especially high start-up rates and the majority of employees in microfirms, knowledge-intensive services (KIS) have a starkly different profile from manufacturing. Results from our structural models indicate that KIS firms benefit from innovation activities through increased labor productivity with highly skilled employees being similarly important compared to R&D for creating innovation output in microfirms. Moreover, the firm size advantage of large firms found for manufacturing almost disappears in KIS, with start-ups and young firms having a higher probability of initiating innovation activities and of successfully turning knowledge into innovation output than mature firms.
Keywords: L25; L26; L60; L80; O31; O33; 330; Microfirms; MSMEs; R&D; Service sector; Innovation; Productivity